Relation de service, rapport social de service : Quelle grille d’analyse ? - Guillaume Tiffon; Pascal Ughetto; Philippe Zarifian (La Nouvelle Revue du Travail)
In a conversation with the Nouvelle Revue du Travail, Pascal Ughetto and Philippe Zarifian address the controversy about service-related analytical grids, by focusing on the preconditions underlying each grid’s particular orientation. The debate follows their contributions to the Controverses special section found in a special issue called “Analysing service relationships and service-based social relationships”